2019
DOI: 10.1016/j.jid.2019.02.021
|View full text |Cite
|
Sign up to set email alerts
|

cis-Khellactone Inhibited the Proinflammatory Macrophages via Promoting Autophagy to Ameliorate Imiquimod-Induced Psoriasis

Abstract: Psoriasis is a chronic inflammatory skin disease with unresolved pathogenesis. Studies on the pathogenesis of psoriasis have been extensively carried out, but treatments are still not satisfactory. In this study, we found improvement after treatment with cis-khellactone, a small molecular natural product, in imiquimod-challenged C57BL/6 mice. cis-Khellactone clearly reduced the level of cytokines in psoriatic skin, including IL-23, TNF-a, IL-1b, and IL-6, while limiting the inhibition of IL-17A, which is produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…Psoriasis is a chronic immune-mediated inflammatory disorder, histologically featuring as abnormal proliferation/differentiation of keratinocytes, excessive angiogenesis, and inflammatory cell infiltration in the dermis [ 100 ]. It has a great impact on the physical and psychological health of patients [ 101 103 ], but few therapeutic strategies are enough to satisfy.…”
Section: Macrophage Polarization In Vascular Dermatosismentioning
confidence: 99%
“…Psoriasis is a chronic immune-mediated inflammatory disorder, histologically featuring as abnormal proliferation/differentiation of keratinocytes, excessive angiogenesis, and inflammatory cell infiltration in the dermis [ 100 ]. It has a great impact on the physical and psychological health of patients [ 101 103 ], but few therapeutic strategies are enough to satisfy.…”
Section: Macrophage Polarization In Vascular Dermatosismentioning
confidence: 99%
“…2c-d), thus disrupting the induction of innate immunity. Moreover, innate cytokines generated from proin ammatory macrophages directly target effector KCs, leading to the production of in ammatory mediators, such as h-BD2, S100A7, CXCL1 and IL-36R [28]. These inotropic cytokines, in turn, recruit excessive macrophages in ltration to form an innate cytokine loop in psoriatic lesions [6,29].…”
Section: Resultsmentioning
confidence: 99%
“…They showed that the inhibition of autophagy in hepatocytes increased inflammation cytokines including IL-18 and IL-1 β . However, Yue et al (2019) and Feng et al (2019) showed that the induction of autophagy ameliorates in vitro psoriasis. Our research showed that the ATG5 gene was upregulated in the in vitro cellular psoriatic model.…”
Section: Discussionmentioning
confidence: 99%